Literatur Review Efektivitas Program Pemberian Makanan Bergizi Gratis (MBG) terhadap Minat Belajar Siswa Tk - Upi Urpiyah; Marthia Ikhlasiah; Lastri Lastri (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
The Free Nutritious Meal Program (MBG) is a free school lunch initiative in Indonesia introduced during the administration of Prabowo Subianto. This study aims to examine the effectiveness of the government's MBG (Free Nutritious Meal) program on kindergarten students' learning interest through a literature review approach. The background of this study is based on the issue of low student learning interest, which is influenced not only by pedagogical factors but also by physical conditions, particularly nutritional intake. This research employed a qualitative approach using a literature review method. The data sources consisted of scientific articles published within the last five years and accessed through Google Scholar. Data were collected through documentation studies, while thematic synthesis was used for data analysis. The findings indicate that the MBG program has a significant positive impact on improving students' learning interest, particularly in terms of attention, motivation, participation, and attendance. The results also reveal that meeting students' physiological needs contributes to their cognitive and emotional readiness to learn. However, the effectiveness of the program is influenced by the quality of its implementation and management in the field. Therefore, more optimal program management and continuous evaluation are needed to maximize its impact on improving the quality of learning.